Norm estimations, continuity, and compactness for Khatri-Rao products of Hilbert Space operators - Arnon Ploymukda; Pattrawut Chansangiam (My University, 2018)
We provide estimations for the operator norm, the trace norm, and the Hilbert-Schmidt norm for Khatri-Rao products of Hilbert space operators. It follows that the Khatri-Rao product is continuous on norm ideals of compact operators equipped with the topologies induced by such norms. Moreover, if two operators are represented by block matrices in which each block is nonzero, then their Khatri-Rao product is compact if and only if both operators are compact. The Khatri-Rao product of two operators are trace-class (Hilbert-Schmidt class) if and only if each factor is trace-class (Hilbert-Schmidt class, respectively).
Keywords: Nuclear operator; Operator norm; Trace class; Holomorphic and Operator Theory